Prophylactic urethral stenting with Memokath® 028SW in prostate cancer patients undergoing prostate 125I seed implants: phase I/II study - Samuel T. Chao; Kenneth Angermeier; Eric A. Klein; Chandana A. Reddy; James C. Ulchaker; Andrew Stephenson; Steven Campbell; Jay P. Ciezki (Journal of Contemporary Brachytherapy, 2011)
Purpose: To study the feasibility/toxicity of urethral stenting with the Memokath® 028SW stent in patients undergoing prostate implant (PI) for prostate adenocarcinoma. Material and methods: An Investigational Device Exemption from the Food and Drug Administration (FDA) and institutional review board (IRB) approval were obtained. Twenty patients enrolled. Baseline American Urological Association (AUA) score was obtained prior to PI. Follow-up information was obtained with weekly phone calls for the first 12 weeks and biweekly calls for the next 12 weeks to assess toxicity and AUA score. Removal of the stent was planned at six months after PI, or earlier due to excessive toxicity/patient request. Results: Median age was 66.5 years. The median prostate volume was 39 cc (range: 10-90). The median baseline AUA score was 7.5 (range: 1-21). Three patients required intermittent self-catheterization (ISC) within 3 days after PI. No patients required ISC beyond day 3 after PI. The median duration of ISC was 1 day (range: 1-2). AUA scores returned to baseline values 6 weeks after PI. The week 6 AUA score was 10 (range: 4-16). Seven patients (35%) underwent early removal because of patient preference. The reasons were: incontinence (n = 3), discomfort (n = 2), hematuria (n = 1), and obstructive symptoms (n = 1). The median time of stent removal in these patients was 13.9 weeks (range: 0.9-21.4). Thirteen patients (65%) had ISC and/or urinary catheterization post stent removal. Median time for ISC use was 10 days (range: 1-90). Conclusions: Urethral stenting with Memokath® in patients undergoing PI was feasible, but resulted in relatively high rate of urinary incontinence and discomfort. Given the adverse effects experienced by patients of this study, further studies should focus only on patients with highest risk of urinary obstruction from PI or those with obstruction needing ISC.